Interactive Learning Media Innovation : The Role Of Education Games In Sharpening Students Problem Solving Skill - Chintani Sihombing; Nur Cahyani Kalil; Windhy Chrysty Tulung; Angelina Helda Semuruk (Journal of Pedagogi, 2025)
This study aims to examine the effectiveness of the application of interactive learning media based on educational games in developing students' problem solving skills. Using a descriptive qualitative approach, data was collected through structured interviews with teachers and students, as well as direct observation of learning activities in the classroom. The results showed that the application of educational games created a more interactive, challenging, and motivating learning atmosphere for students to think critically. During the learning process, students showed improvement in the ability to analyze problems, design alternative solutions, evaluate the results of decisions, and dare to take the initiative in solving various problem solving situations simulated through games. Teachers also noted the development of independent thinking, increased collaboration between students, and students' courage in expressing their opinions during the learning session. Educational games are proven to provide meaningful learning experiences through the application of the principles of constructivism, experiential learning, and gamification, which allow students to actively build understanding through direct involvement in problem solving. This research emphasizes that educational games have significant potential as interactive learning innovations that support the strengthening of problem solving competencies as one of the key skills in facing 21st century learning challenges